Bilateral Oval and Round Window Atresia on CT Temporal Bone: A Rare Anomaly Clinically Mimicking Otosclerosis in an Adult - Manzoor Ahmed; Yogesh Indrasen More; Shaik Irfan Basha (Case Reports in Radiology)
We present a rare adult case of bilateral oval and round window atresia. Clinical and audiologic findings were suggestive of otosclerosis. High resolution CT Temporal bones showed unequivocal findings of bilateral oval and round window atresia. Atresia of these windows is a rare temporal bone anomaly. Presentation as an adult can confound the clinicians and warranting a closer look on the CT for atretic windows and subtle signs of otosclerosis in patients with conductive hearing loss.